L'elevage des petits ruminants dans le monde - International Livestock Centre for Africa (1980)
Analysis of small ruminant production in developed and developing countries, particularly sheep & goat distribution in the world, meat, milk and wool regional distribution, trends of declining and growth production of small ruminants, and price ratios for wool, w. data on world meat & livestock prices.